Website Management Training Tourism Village in Sumber Pakel Padang District Lumajang - Riza Bahtiar (LPPM of NAROTAMA UNIVERSITY, 2018)
Such sites are generally in Indonesia, Lumajang has a tourist location that has the concept of Village Tourism. One was found in the village of Padang District Responsibility. Tourism is developed in this area is a tourist village Pakel Source. Some tours are being designed is natural tourism, fishing, cultural tours, culinary tours, tourist SMEs, farm tours, farm tour and plantation tours. The purpose of the Community Services is (1) creation and management of websites Village Tourism Resources Pakel as a promotional tool that is effective and efficient, as well as training to manage the website, (2) training of the drafting of the products that will be promoted on the site. This event was held for one month. Method of implementation is through training, discussion and practice. Also, physical assistance for making tools in the form of internet access and cable modem connections to facilitate the capture signal or network. The goal of this activity is a member Pokdarwis Sumber Pakel as manager of the website. The results of this activity are the implementation of the training activities of managing a site, a survey for the promoted products are posted on the web as well as drafting and grammar. There was also an increase in the means for support in managing the Sumber Pakel Tourism Village website.